Assessment of phototherapy-induced hypocalcemia and its correlation with urinary calcium excretion in term and preterm newborns with neonatal hyperbilirubinemia: A cross-sectional study with controls - Gupta, Raksha; Singh, Davinder; Yadav, Meetu; Panda, Prateek Kumar; Nagaraj, Niranjan; Bana, Sailen Kumar (Indian Journal of Child Health, 2018)
Introduction: Although hypocalcemia is often proposed to be associated with phototherapy in both term and preterm newborns, its exact incidence, clinical significance, and underlying mechanism still remain to be elucidated. Objective: The objective of this study was to determine the prevalence of hypocalcemia and its etiopathogenesis in terms of urinary calcium excretion. Methods: This study was carried out in a tertiary care center in North India with 50 neonates (29 term and 21 preterm) in the test group receiving single surface phototherapy. The other 50 age, sex, and gestational age-matched neonates were taken as controls who did not receive phototherapy. Serum calcium levels at 0 and 48 h and urinary calcium/creatinine ratio (mg/mg) at 0 and 24 h of starting phototherapy were determined in both the groups and compared. Results: Total 12 preterm (57.1%) and 9 term newborns (31%) developed hypocalcemia after 48 h of phototherapy. The mean difference of serum ionized calcium between two groups was statistically significant at 48 h (4.58 mg/dl in the test group vs. 4.94 mg/dl in the control group, p<0.001). Percentage change in mean of urinary calcium/creatinine ratio at 24 h from baseline was 1.39% in the control group while it was 60.7% in the test group with statistically significant difference (p<0.001) between two groups. Only a weak negative correlation between serum ionized calcium and urinary calcium/creatinine ratio with correlation coefficient r=?0.316 could be established in the study among both term and preterm neonates. Conclusion: Both preterm and term neonates undergoing phototherapy are at increased risk for hypocalcemia and increased urinary calcium excretion. A universal recommendation regarding calcium supplementation in neonates undergoing phototherapy is yet to be established but seems like a reasonable intervention.